Naturally acquired antibody responses to recombinant Pfs230 and Pfs48/45 transmission blocking vaccine candidates. Issue 1 (July 2015) - Jones, Sophie; Grignard, Lynn; Nebie, Issa; Chilongola, Jaffu; Dodoo, Daniel; Sauerwein, Robert; Theisen, Michael; Roeffen, Will; Singh, Shrawan Kumar; Singh, Rajesh Kumar; Singh, Sanjay; Kyei-Baafour, Eric; et al.
Summary Objectives Pfs48/45 and Pfs230 are Plasmodium falciparum sexual stage proteins and promising malaria transmission-blocking vaccine candidates. Antibody responses against these proteins may be naturally acquired and target antigens may be under selective pressure. This has consequences for the future evaluation of vaccine immunogenicity and efficacy in populations naturally exposed to malaria. Methods We determined naturally acquired antibody responses to the recombinant proteins Pfs48/45-10C and Pfs230-230CMB in children from three malaria endemic settings in Ghana, Tanzania and Burkina Faso. We also examined genetic polymorphisms in the P. falciparum gene pfs48/45. Results Antibody prevalence was 1.1–18.2% for 10C and 6.7–18.9% for 230CMB. In Burkina Faso we observed evidence of an age-dependent acquisition pattern for both 10C (p < 0.001) and 230CMB (p = 0.031). Membrane feeding assays on a separate dataset demonstrated an association between functional transmission reducing activity and antibody prevalence for both 10C (p = 0.017) and 230CMB (p = 0.049). 17 single nucleotide polymorphisms were found in pfs48/45 (from 126 samples), with 5 non-synonymous SNPs in the Pfs48/45 10C region. Conclusions We conclude there are naturally acquired antibody responses to both vaccine candidates which have functional relevance by reducing the transmissibility of infected individuals. We identified genetic polymorphisms, in pfs48/45 which exhibited geographical specificity.